Life Cycle Assessment of current and prospective waste management systems in Brazil - Lima, Priscila de Morais (2019)
The increase of Municipal Solid Waste (MSW) generation along with the current inadequate waste management and the issue of the Solid Waste National Policy (PNRS) in 2010, have brought a bigger concern in regards to the matter to Brazilian municipalities. Besides all the demands of the Policy, improper waste disposal sites still represent 40% of the destination of the waste collected in Brazil. In addition, only about 3.6% of recyclables are currently recovered. Campo Grande is the state capital of Mato Grosso do Sul and has a sanitary landfill with two more years of lifespan. The city has recently published its new tool to aid waste management – the Selective Collection Plan (PCS), which is comprised of planning and goals for the next 20 years. Facing this situation, the aim of this research was to analyze and compare different waste management systems for Brazil (Chapter 2) and Campo Grande (Chapter 3). A consequential Life Cycle Assessment (LCA) was employed, with the software EASETECH for modelling. The general results showed that the improper disposal sites (i.e. dumps) have the highest environmental impacts due to the untreated landfill gas and leachate. The combination of high recycling rates and low amounts of waste disposed in landfills presented overall good performance in both cases. From all the scenarios assessed, the best performance was achieved by anaerobic digestion of the biowaste, with biogas utilization as fuel substitute, combined with a material recovery facility and a mixed waste mechanical biological treatment, with residue derived fuel directed to cement kilns avoiding coke combustion. In conclusion, the environmental awareness must be raised towards the population and the decision-makers are entitled to the changes that need to happen in order to decrease the environmental impacts of the systems and comply with the Brazilian waste legislation.